Do those who talk more learn more? The relationship between student classroom talk and student achievement. (October 2019) - Sedova, Klara; Sedlacek, Martin; Svaricek, Roman; Majcik, Martin; Navratilova, Jana; Drexlerova, Anna; Kychler, Jakub; Salamounova, Zuzana
Abstract: There have been efforts to investigate the link between classroom talk and student achievement for some time. However, studies considering individual student participation in classroom talk have thus far been rare. The research reported in this study was carried out on 639 ninth grade students at Czech middle schools. Observations took place in language arts lessons; talk time and the number of utterances with reasoning were recorded for each student. Achievement was measured using a standardized reading literacy test. The results confirmed a strong link between a given student's talk time and number of utterances featuring reasoning and that student's achievement. As for student talk time, a connection at the classroom level was also identified – students in talkative classrooms had better results. However, there was not a connection between utterances with reasoning and better results at the classroom level. A positive link between individual participation and achievement was observed in all students regardless of socio-economic background or gender. Highlights: We measured individual participation in classroom talk of ninth grade students in language arts lessons. We explored the relationship between participation and student achievement in reading literacy. The more a student talked in class, the better they performed in a reading literacy test. The more a student engaged in reasoning in class, the better their results in a reading literacy test. These links applied regardless of student socio-economic background or gender.